Mindfulness Program untuk Meningkatkan Quality Of Life dan Coping Religius Pasca Pandemic pada Lansia di Panti Sosial Tresna Werdha Yogyakarta - Rofiqoh Fadhliyah; Nisrin Alifah; Nabila Putri Alifah; Shakeela Rohmatunnisa; Muhammad Erwan Syah (Guidena)
This research aims to determine the effect of the Mindfulness and Religious Coping Program on the Post-Pandemic Quality of Life for older people at the Tresna Werdha Social Home in Yogyakarta. This research uses research methods, namely descriptive quantitative and qualitative approaches, with the research design using one group pretest-posttest design. This study's population was older people at Werdha Social Home in Yogyakarta. Researchers used purposive sampling as a subject-determination technique to obtain subjects in this study. The number of subjects in this study was 44 people. This is done because of the unique characteristics of the subject. The measuring instrument used in this research is an adaptation of the Quality of Life and Religious Coping scales. Data analysis in this study used a Paired Sample T-Test. The research results show that the Mindfulness program positively affects Mindfulness and Religious Coping for Post-Pandemic Quality of Life in older people at the Tresna Werdha Social Home. The results obtained are a t value of -0.942 with a significance value (Sig(2-tailed)) of 0.352, which means the value is more significant than 0.05 (p>0.05).